KAJIAN PENGELOLAAN LIMBAH RUMAH SAKIT GRHA ULTIMA MEDIKA DI KOTA MATARAM, NTB - Azwaruddin Azwaruddin (Yayasan Akrab Pekanbaru, 2018)
Hospitals as a means of health effort that organizes health services that include outpatient services, hospitalization, emergency care, medical services, and non-medical. Hospital operations will produce waste that can cause environmental pollution. Therefore it is necessary to control the disposal of solid waste, liquids and gases released into the environment. This study Knowing of Assessment and Evaluation of waste management Grha Ultima Medika Hospital. The type of research is descriptive research procedure is a form of preparatory research, secondary data collection, and the primary data collection in the field include identification of solid waste of medical and non-medical, identification of clean water usage, water quality data of waste (outlet) and the identification of sources of emissions and data emissions or ambient air quality. The results of the assessment and evaluation was conducted in the management of solid waste in the range of 22% of the total 45 votes, for liquid waste is in the range 58% of the total value of 45 while waste gas is in the range of 20% of the 45 total. Keywords : Assessment, Hazardous Solid, Liquid and Gas